TINGKAT STRES KELUARGA DI MASA NEW NORMAL - Indah Puspitasari; Aliffia, Aliffia; Yusrini, Yusrini (Jurnal Ilmiah Keperawatan IMELDA, 2023)
Introduction: The current pandemic is due to the presence of the coronavirus disease (COVID-19), which has been ongoing for quite some time. The health crisis of the COVID-19 pandemic causes psychological changes such as fear, anxiety, depression, and stress. This shock is felt by the whole of society. But many people are experiencing contagious fears because of limited or incorrect knowledge about COVID-19. The level of stress during the pandemic has been surveyed by both health care personnel and individuals in Indonesia, but there has been no study of stress levels in families, especially in Bekasi City. Excessive stress can interfere with a person's ability to cope with the environment. Objective: Find out the stress level of the family in normal times based on demographic characteristics. Methods: The design of this research is analytical and descriptive. Using univariate statistical tests. The measurement of this research uses a questionnaire. This research instrument uses the instruments produced by lead researchers Premier, Wade, May, Jenkins, and Dillon of the CRAMPED (DB) study and laboratory members at the University of Waterloo, Canada (2021) on The COVID-19 Family Stressor Scale: Validation and Measurement. Invariance in Female and Male Caregivers: The questionnaire has been modified by researchers because of the addition of words or sentences adapted to the conditions of the COVID-19 pandemic in Indonesia. Results: In this study in Kelurahan Margahayu, respondents who experienced increased stress, the majority aged 25–34 years, were 60.5%; males were 52.0%; husbands were 52.0%; working as private officers was 73.0%; and experiencing average stress was 38.3%. Conclusion: The stress levels in the family are mostly mild, with the majority of family heads being male and aged 25–34.